2019
DOI: 10.3892/mmr.2019.10753
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling analysis reveals that the long non‑coding RNA uc.412 is involved in mesangial cell proliferation

Abstract: Hyperproliferation of mesangial cells (MCs) is the central pathological feature observed in certain human renal diseases. Furthermore, the long non-coding RNA uc.412 is regulated by transforming growth factor β1 in mesangial cells in vitro. The present study aimed to investigate whether uc.412 serves a role in renal fibrosis and whether it may be considered as a therapeutic target in mesangial proliferative kidney diseases. The results demonstrated that uc.412 overexpression significantly increased MC prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As long-established cell lines in literature, mesangial cells and podocytes are important biological samples to determine the best reference gene -many researchers in the field are focused on these structures (42)(43)(44)(45)(46)(47) and the data provided by our work could potentially influence many studies, providing support to avoid wrong interpretation of results and its influence in downstream analysis and further conclusions.…”
Section: Discussionmentioning
confidence: 88%
“…As long-established cell lines in literature, mesangial cells and podocytes are important biological samples to determine the best reference gene -many researchers in the field are focused on these structures (42)(43)(44)(45)(46)(47) and the data provided by our work could potentially influence many studies, providing support to avoid wrong interpretation of results and its influence in downstream analysis and further conclusions.…”
Section: Discussionmentioning
confidence: 88%
“…We found that ELAVL1 was the binding protein for uc.412 (Figure 4a). Previous results using sequencing also showed that ELAVL1 expression was elevated after uc.412 overexpression [14]. Therefore, ELAVL1 was identi ed as the appropriate binding protein for uc.412.…”
Section: Elavl1 Is the Target Of Lncrna Uc412mentioning
confidence: 93%
“…Meanwhile, Sun et al showed that lncRNA Erbb4-IR, which was induced by TGF-β1, promoted renal brosis via a Smad3-dependent mechanism [13]. Moreover, by using RNA-seq, we previously identi ed that lncRNA uc.412 was upregulated during the process of MCs proliferation [14].…”
Section: Introductionmentioning
confidence: 99%
“…As long-established cell lines in the literature, mesangial cells and podocytes are important biological samples to determine the best reference gene-many researchers in the field are focused on these structures [54][55][56][57][58][59], and the data provided by our work could potentially influence many studies, providing support to avoid incorrect interpretation of results and their influence in downstream analysis and further conclusions.…”
Section: Plos Onementioning
confidence: 95%